Understanding the Sources of Spatial Disparity and Convergence : Evidence from Bangladesh - Shilpi, Forhad (World Bank, Washington, DC, 2013)
This paper utilizes the mixed effects model to measure and decompose spatial disparity in per capita expenditure in Bangladesh between 2000 and 2010. It finds a significant decline in spatial disparity in urban areas and the country as a whole but no substantial change in rural areas. The decomposition analysis indicates that average years of education, the percentage of households with electricity connections, and phone ownership account for most of the spatial variations in welfare. Spatial convergence in urban areas can be explained primarily by the expansion of electricity and phone networks for household use. Improved access to these services had little effect on spatial disparity in rural areas. This paper offers several explanations for the difference in convergence rates between urban and rural areas.